Clodronate Treatment Prevents Vaginal Hypersensitivity in a Mouse Model of Vestibulodynia - Castro, Joel; Harrington, Andrea M.; Chegini, Fariba; Matusica, Dusan; Spencer, Nick J.; Brierley, Stuart M.; Haberberger, Rainer V.; Barry, Christine M. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction: Improved understanding of vulvodynia pathophysiology is required to develop appropriately targeted treatments. Established features include vaginal hyperinnervation, increased nociceptive signaling and hypersensitivity. Emerging evidence indicates macrophage-neuron signaling contributes to chronic pain pathophysiology. Macrophages are broadly classified as M1 or M2, demonstrating pro-nociceptive or anti-nociceptive effects respectively. This study investigated the contribution of macrophages in nociceptive signaling in a mouse model of vulvodynia. Methods: Microinjection of complete Freund’s adjuvant (CFA) induced mild chronic vaginal inflammation in C57Bl/6J mice. A subgroup was treated with the macrophage depleting agent clodronate. Control mice received saline. After 7 days, immunolabelling for PGP9.5, F4/80+CD11c+ and F4/80+CD206+ was used to compare innervation density and presence of M1 and M2 macrophages respectively in experimental groups. Nociceptive signaling evoked by vaginal distension was assessed using immunolabelling for phosphorylated MAP extracellular signal-related kinase (pERK) in spinal cord sections. Hyperalgesia was assessed by visceromotor response to graded vaginal distension. Results: CFA led to increased vaginal innervation (p < 0.05), increased pERK-immunoreactive spinal cord dorsal horn neurons evoked by vaginal-distension (p < 0.01) and enhanced visceromotor responses compared control mice (p < 0.01). Clodronate did not reduce vaginal hyperinnervation but significantly reduced the abundance of M1 and M2 vaginal macrophages and restored vaginal nociceptive signaling and vagina sensitivity to that of healthy control animals. Conclusions: We have developed a robust mouse model of vulvodynia that demonstrates vaginal hyperinnervation, enhanced nociceptive signaling, hyperalgesia and allodynia. Macrophages contribute to hypersensitivity in this model. Macrophage-sensory neuron signaling pathways may present useful pathophysiological targets.